1992
DOI: 10.21273/jashs.117.6.906
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Silicon Sprays Inhibit Powdery Mildew Development on Grape Leaves

Abstract: The effect of root or leaf applications of soluble Si on severity of grape (Vitis vinifera L.) powdery mildew [Uncinula necator (Schwein) Burrill] was determined. On potted plants, root-feeding at 1.7 mm Si had no effect on disease severity, but foliar sprays at 17 mm Si substantially reduced the number of mildew colonies that developed on inoculated leaves. Scanning electron micrographs showed that, on Si-spray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(86 citation statements)
references
References 10 publications
4
74
2
4
Order By: Relevance
“…Although the nature of the P. rapae extract has not been identified, the inherent compound possessed basic characteristics as an elicitor that reduces cucumber damage from C. orbiculare. It agrees with previous reports that foliar-applied Si significantly suppressed downy mildew (Bowen et al, 1992). The P. rapae extract could inhibit the conidium germination of C. orbicular but not the mycelium growth in vitro at the concentration used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Although the nature of the P. rapae extract has not been identified, the inherent compound possessed basic characteristics as an elicitor that reduces cucumber damage from C. orbiculare. It agrees with previous reports that foliar-applied Si significantly suppressed downy mildew (Bowen et al, 1992). The P. rapae extract could inhibit the conidium germination of C. orbicular but not the mycelium growth in vitro at the concentration used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…There are numerous reports on Si suppressing plant diseases and pests, such as blast and sheath blight in rice (Datnoff et al 1997;Seebold et al 2001;Rodrigues et al 2003;Cai et al 2008), powdery mildew in cucumber, Arabidopsis in wheat Fauteux et al 2006;Côté-Beaulieu et al 2009), Eldana saccharina in sugarcane (Keeping and Meyer 2002), and rust in cowpea (Heath and Stumpf 1986). Evidence showed that siliconmediated resistance to the pathogen is associated with the higher deposit of silicon in leaf and the activation of host defense response (Bowen et al 1992;Kim et al 2002;Rémus-Borel et al 2005;Cai et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Its major role is to increase the plant resistance to pathogens, pests and diseases, especially to fungal diseases, thereby contributing to plant health and yield improvement (Bowen et al 1992;Raven 2003;Henriet et al 2006). One of the most important beneficial effects of silicon on plant growth is related to increased resistance under water stress conditions (Ma et al 2004;Sacała 2009).…”
mentioning
confidence: 99%